Thermally induced shape memory behavior, enzymatic degradation and biocompatibility of PLA/TPU blends: "Effects of compatibilization". (July 2017) - Dogan, S.K.; Boyacioglu, S.; Kodal, M.; Gokce, O.; Ozkoc, G.
Abstract: Poly(lactic acid) (PLA)/thermoplastic polyurethane (TPU) blends were melt-mixed and compatibilized to investigate their biocompatibility, biodegradability and thermally induced shape memory properties. The blend compositions were PLA/TPU: 80/20 (20TPU) and PLA/TPU: 50/50 (50TPU). 1, 4-phenylene diisocyanate (PDI) was used in order to compatibilize the components reactively. The PDI composition was 0.5, 1, 3% by weight. Biodegradability was assessed by enzymatic degradation tests. Biocompatibility was investigated through in-vitro cell-culture experiments. Shape memory tests exhibited that 20TPU blends have higher recovery ratio than that of 50TPU blends. It was observed that the shape recovery ratio was enhanced by the addition of PDI. The highest shape recovery ratio was obtained at 3%PDI in 20TPU blends. Enzymatic biodegradability tests showed that the increasing TPU content decreased the biodegradability of the blends. It was found that compatibilization slowed down the enzymatic degradation of PLA/TPU blends. In-vitro cell-culture experiments indicated that all blends were biocompatible, and no evidence of cytotoxicity was observed. Graphical abstract: Highlights: Thermally responsive PLA/TPU blends were successfully prepared. Compatibilization by a diisocyanate improved the shape memory properties. Increasing TPU content and compatibilization retarded the enzymatic degradation. In vitro cell-culture tests showed non-toxicity and biocompatibility.